Understanding Complex Landscape of Memory, Commemoration, and Culture with Location-based Technology - Mink, Andy Mink; Bunin, Chris; Dunlevy, Matt; Lentz, Christian (VNU Journal of Science: Social Sciences and Humanities; Vol 32 No 1S, 2016)
Abstract: Current and emerging technologies provide increasing levels of situation- and location based information. It is critical in an increasingly information- and knowledge-based society that visitors, citizens, and students are prepared to access, think critically about, and process that information. This panel will illustrate a series of proof of concept projects that leverage the emerging technologies of location-based technologies to enhance the educational experience at sites in the United States and Europe. This projects leverage technology to not only access information, but to build materials for formal (classroom-based) as well as informal (site-based) learning. These materials have value for teachers and students in classrooms across America, and they also be important additions to the on-site and at-memorial visitor experience.